ANALISIS NILAI TAMBAH BUAH SALAK SEBAGAI BAHAN BAKU DODOL SALAK PADA UD MANDIRI DI DESA PANGU I KECAMATAN RATAHAN KABUPATEN MINAHASA TENGGARA - Juliana ., Raranta; Eyverson ., Ruauw; Nordy Fritsgerald Lucky Waney (AGRI-SOSIOEKONOMI, 2018)
The objective of this research is to analyze and to compare the added value and profit of processingÂ â€œsalakâ€ to â€œdodol salakâ€ based on type of harvesting. This research was conducted for 3 months from April toÂ June 2018 at UD Mandiri in Pangu I Village, Ratahan District, Southeast Minahasa. Data used are primaryÂ data obtained by interviewing to business owner using questionnaires. Data analysis of the data used is addedÂ value with the formula of NTp = (NTp = Na - (Bb + Bp + Bbp) and profit analysis using the formula Ï€ = (Ï€ =Â TR â€“ TC). Results showed that businnes of â€œdodol salakâ€ generate added value at big harvest (panen raya) isÂ Rp. 19,399,652.78, at medium harvest (panen sedang) is Rp. 18,649,652.78, and at small harvest (panen kecil)Â is Rp. 17,749,652.78. The business profits of â€œdodol salakâ€ at the big harvest (panen raya) is Rp.8,499,652.78, at medium harvest (panen sedang) is Rp.7,749,652.78, and at small harvest (panen kecil) is Rp.Â 6,849,652.78. The highest added value of â€œdodol salakâ€ at big harvest (panen raya) was 9.30 percent greaterÂ than at small harvest (panen kecil), and 4.02 percent that at the medium harvest (panen sedang). The highestÂ business profit from â€œdodol salakâ€ at the big harvest (panen raya) which was greater 24.09 percent than atÂ the small harvest (panen kecil), and 9.68 percent than at the medium harvest (panen sedang). *llr+eprm*.